2019
DOI: 10.1002/acr.23704
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Knee Load and Pain: Within‐Patient, Between‐Knees, Case–Control Study in Patients With Knee Osteoarthritis

Abstract: When between-patient confounding is minimized, there is a strong association between medial knee load and increased knee pain during walking. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Using this method, in 2 large knee OA cohorts, researchers showed that knee pain was strongly associated with radiographic tibiofemoral OA (11). Similar approaches have since been used to better understand various knee-specific determinants of pain in knee OA (12,13), and such approaches would be well-suited to evaluating joint-level determinants of anterior knee pain.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, in 2 large knee OA cohorts, researchers showed that knee pain was strongly associated with radiographic tibiofemoral OA (11). Similar approaches have since been used to better understand various knee-specific determinants of pain in knee OA (12,13), and such approaches would be well-suited to evaluating joint-level determinants of anterior knee pain.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies in the past year used a stimulus-response model, highlighted for its relevance to OA by Andriacchi in 2012 75 , to investigate how pain after a bout of walking was related to jointlevel biomechanics. Birmingham et al examined KAM peaks and impulses after a 6-min walking bout in 256 individuals with radiographic and symptomatic medial compartment knee OA, but who had discordant pain ratings between knees 76 . Higher KAM peaks and impulses were related to a greater risk of pain during the walking bout (OR ¼ 2.4, 95% CI: 1.8e3.3 and 6.6, 95% CI: 3.5e12.7, respectively), and this relationship was most prominent in the highest knee load quartile.…”
Section: Pain and Mechanicsmentioning
confidence: 99%
“…Birmingham и соавт. [37] изучили симптоматику у 265 больных ОА коленного сустава и отметили связь между выраженностью нагрузки и интенсивностью боли в суставах. Заметную роль нарушений биомеханики в развитии клиники и прогрессировании ОА коленного сустава показывают результаты масштабных исследований MOST (многоцентровое исследование ОА) и «Инициатива остеоартрита».…”
Section: фенотип скелетно-мышечной боли связанный с движением («мехаunclassified